The role of multi modality imaging in selecting patients and guiding lead placement for the delivery of cardiac resynchronization therapy. (1st February 2017) - Behar, Jonathan M; Claridge, Simon; Jackson, Tom; Sieniewicz, Ben; Porter, Bradley; Webb, Jessica; Rajani, Ronak; Kapetanakis, Stamatis; Carr-White, Gerald; Rinaldi, Christopher A
ABSTRACT: Introduction : Cardiac resynchronization therapy (CRT) is an effective pacemaker delivered treatment for selected patients with heart failure with the target of restoring electro-mechanical synchrony. Imaging techniques using echocardiography have as yet failed to find a metric of dyssynchrony to predict CRT response. Current guidelines are thus unchanged in recommending prolonged QRS duration, severe systolic function and refractory heart failure symptoms as criteria for CRT implantation. Evolving strain imaging techniques in 3D echocardiography, cardiac MRI and CT may however, overcome limitations of older methods and yield more powerful CRT response predictors. Areas covered : In this review, we firstly discuss the use of multi modality cardiac imaging in the selection of patients for CRT implantation and predicting the response to CRT. Secondly we examine the clinical evidence on avoiding areas of myocardial scar, targeting areas of dyssynchrony and in doing so, achieving the optimal positioning of the left ventricular lead to deliver CRT. Finally, we present the latest clinical studies which are integrating both clinical and imaging data with X-rays during the implantation in order to improve the accuracy of LV lead placement. Expert commentary : Image integration and fusion of datasets with live X-Ray angiography to guide procedures in real time is now a reality for some implanting centers. Such hybrid facilities will enable users to interact with images, allowing measurement, annotation and manipulation with instantaneous visualization on the catheter laboratory monitor. Such advances will serve as an invaluable adjunct for implanting physicians to accurately deliver pacemaker leads into the optimal position to deliver CRT.